Healthy eating habits in college students (Revista de Investigaciones Universidad del Quindío, 2021)
A healthy diet is a determining factor for the good health of people at any stage of their life cycle. This diet should contain essential nutrients, in addition to being varied and appropriate to the age, weight, height, sex, and physical condition of each person.  The purpose of this research  is to identify the healthy eating habits of university students, as well as to determine whether there was a change in their habits as a result of the Covid-19 pandemic. Data were collected from 408 students through a structured measurement instrument, the Kidmed test. The statistics used were nonparametric tests: Mann-Withney and Kruskal-Wallis. The results obtained were: the students presented an average diet and there is a need to improve eating habits. Gender differences were found, women presented a higher consumption of fruits, vegetables, rice and fish than men, in terms of age the positive habits such as: consume fruit, vegetables, legumes, nuts, predominate students in an age range of 20 to 23 and older than 25 years. The 54.53% of the students have negative habits that include: eating fast food, not eating breakfast, or eating industrial pastries for breakfast and consuming sweets.
Keywords: Healthy eating; Kidmed test; college students